Konsep Pemikiran Pendidikan Islam dan Sistem Pendidikan Islam Menurut Hadratussyaikh KH M Hasyim Asy’ari - Muhammad Ramdoni; Agus Suryana; Ernawati Ernawati (Transformasi Manageria: Journal of Islamic Education Management, 2021)
This study discusses the thought of Islamic Education in the perspective of Kiai Hasyim Asy'ari. To find out the extent to which various changes and developments in Islamic education should make us always motivated to review and improve the quality of ourselves, in order to increase the quality and quantity of Islamic education in Indonesia. Because basically since the Indonesian state was born in 1945, education has become the cornerstone of one of the pillars of the nation's progress. Education is like a womb in which there are genes with a neat composition with all the seeds of existing abilities. Therefore it is necessary to have motivation in an effort to explore potential, good direction and planning in the development of education. From the results of the research conducted, it shows that K.H Hasyim Ash'ari's thoughts that talk about education emphasize more on educational ethics. Because ethics is more important than intelligence. Expertise in hadith is colored in the aspect of education. So that some of his works can change the situation at that time and experience changes and rapid development of an education.